PERAN AKUNTANSI FORENSIK DALAM MENGUNGKAP KASUS KECURANGAN KEUANGAN DI PERUSAHAAN PUBLIK - Terssia Putri Sari (Adisam Publisher, 2024)
This research addresses the issue of financial fraud that frequently occurs in public companies, causing significant financial losses and damaging corporate reputation. The purpose of this study is to examine the role of forensic accounting in uncovering financial fraud cases. The method used is a literature review through the examination of various academic sources, case reports, and related industry publications. Data analysis is conducted using a qualitative approach, evaluating findings from multiple studies and case reports. The results indicate that forensic accounting, through meticulous investigative techniques and the use of data analysis technology, can accurately identify and present evidence of fraud. This study also confirms that implementing forensic accounting strengthens internal controls and enhances financial transparency within companies. In conclusion, forensic accounting plays a crucial role in detecting and preventing financial fraud in public companies, while also providing strategic recommendations for future risk mitigation. Proactive application of forensic accounting is essential for public companies to maintain integrity and trust among various stakeholders. This research reinforces the importance of integrating forensic accounting into risk management and internal audit processes.